2002
DOI: 10.1152/jn.00104.1999
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of Auditory Cortex in Frequency Processing and Pitch Perception

Abstract: . Microelectrode studies in nonhuman primates and other mammals have demonstrated that many neurons in auditory cortex are excited by pure tone stimulation only when the tone's frequency lies within a narrow range of the audible spectrum. However, the effects of auditory cortex lesions in animals and humans have been interpreted as evidence against the notion that neuronal frequency selectivity is functionally relevant to frequency discrimination. Here we report psychophysical and anatomical evidence in favor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(80 citation statements)
references
References 110 publications
4
73
0
3
Order By: Relevance
“…It is possible that disruption of local cortical activity alone could suppress hearing, although it is generally agreed that in humans (Tramo et al, 2002;Kaga et al, 2000;Hausler and Levine, 2000;Penfield and Perot, 1963) and in laboratory animals (Heffner and Heffner, 1986;Heffner, 1997;Colombo et al,1996;Whitfield et al, 1978) that unilateral destruction of auditory cortex of the STG does not result in deafness. More likely, hearing suppression is the result of activating corticofugal efferent pathways that project to auditory thalamic, midbrain and brainstem structures, and possibly the cochlea (Hazama et al, 2004;He, 2003;Jacomme et al, 2003, Suga andPandya et al, 1994;Weedman and Ryugo, 1996a,b).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that disruption of local cortical activity alone could suppress hearing, although it is generally agreed that in humans (Tramo et al, 2002;Kaga et al, 2000;Hausler and Levine, 2000;Penfield and Perot, 1963) and in laboratory animals (Heffner and Heffner, 1986;Heffner, 1997;Colombo et al,1996;Whitfield et al, 1978) that unilateral destruction of auditory cortex of the STG does not result in deafness. More likely, hearing suppression is the result of activating corticofugal efferent pathways that project to auditory thalamic, midbrain and brainstem structures, and possibly the cochlea (Hazama et al, 2004;He, 2003;Jacomme et al, 2003, Suga andPandya et al, 1994;Weedman and Ryugo, 1996a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Diese Strukturen sind entscheidend in emotionale Prozesse (Amygdala), in die Evaluation sensorischer Information (Orbitofrontalkortex) und in die Kontrolle emotionalen Verhaltens (ebenfalls Orbitofrontalkortex) involviert. Im auditorischen Kortex (höchstwahrscheinlich sowohl in primären als auch in angrenzenden sekundären auditorischen Feldern) werden akustische Merkmale wie Tonhöhe, Tonchroma, Klangfarbe, Intensität und Rauhigkeit extrahiert 1 (Tramo et al, 2002;Patel & Balaban, 2001;Schönwiesner et al, 2002;Warren et al , 2003;Fishman et al, 2001). Die diesen Extraktionen zugrundeliegenden Operationen sind elektrisch vermutlich in sog.…”
Section: Frühe Verarbeitungsstufenunclassified
“…In cats, bilateral lesions of the entire auditory cortex impair the discrimination of changes in the pitch of the missing fundamental, but not changes in frequency alone, demonstrating the necessity of auditory cortex in pitch perception [46]. Humans with partial auditory cortex lesions have also been shown to have poorer pitch discrimination [47], with lesions of the right auditory cortex showing larger deficits [48][49]. Behavioral studies in patients with auditory cortex lesions have further suggested that lesions anterior to primary auditory cortex result in more pronounced deficits in pitch discrimination [49].…”
Section: A Pitch-processing Center In Primate Auditory Cortexmentioning
confidence: 99%